P41 Diet quality across adulthood and physical performance in older age: findings from the MRC National Survey of Health and Development. (13th September 2016) - Westbury, LD; Syddall, HE; Cooper, R; Kuh, D; Cooper, C; Sayer, AA; Robinson, SM
Abstract : Background: Studies have reported associations between healthier diets and better physical performance among older people. However, little is known about the influence of diet quality throughout adulthood on physical performance in later life. Therefore, we aimed to examine the relationship between diet quality at ages 36, 43, 53 and 60–64 years and physical performance at age 60–64 among 927 individuals (with complete dietary data) who participated in the MRC National Survey of Health and Development (NSHD). Methods: At ages 36 to 60–64, NSHD participants recorded all food and drinks items consumed over 5 days in diaries; items were categorised into 45 food groups. Principal component analysis of the food groups at age 60–64 was used to examine dietary patterns; the first component reflected a healthy dietary pattern and was used to derive diet scores at each age (with higher scores indicating healthier diets). Linear regression was then used to examine the association between diet scores at each age and measures of physical performance and strength at 60–64: grip strength (kg); chair rise speed (stands/minute); one-legged standing balance time (s); and timed up-and-go (TUG) speed (m/s). Gender- and fully-adjusted models, accounting for anthropometric, lifestyle and socio-demographic characteristics, were implemented. The association between diet quality at 60–64 and physical performance, conditional on earlier diet quality, was also examined. Results: Diet quality was moderately correlated between ages in adulthood (0.42< r < 0.66). However, mean diet scores increased from age 36 to age 60–64 among men and women. In gender-adjusted analysis, healthier diet quality at each age was associated (p < 0.01) with better performance on all physical tests except grip strength. Associations between diet quality at age 60–64 and chair rise speed and standing balance time remained significant (p < 0.02) in fully-adjusted analysis; for example, a unit increase in diet score was associated with 0.40 (95% CI: 0.07, 0.73) stands/min increase in chair rise speed. Higher diet quality than expected at age 60–64, given earlier diet quality, was associated (p < 0.008) with better chair rise speed and standing balance time. Conclusion: Higher diet quality across adulthood is related to better physical performance at age 60–64. Although diet quality 'tracks', current diet appears particularly important, and is associated with some physical performance measures even after accounting for potential confounders and earlier diet quality. Encouraging healthier diets in older age may make an important contribution to improving physical performance and promoting healthy ageing.